PENINGKATAN KAPASITAS APARATUR DESA MELALUI PELATIHAN MANAJEMEN KELEMBAGAAN DESA BAGI SEKRETARIS DESA - Mulyana, Nana; Meiliyana, Meiliyana; Hermawan, Dedy (Prosiding Pengabdian FISIP Unila, 2012)
Implementation Activities  Community Services  is  located in the District  Jatiagung South Lampung.  The method used  in the form of  lectures  and discussion  /  FAQ. Thus, the  evaluation design  used was  a quantitative  evaluation  through pre-test and post-test  and evaluation qualitatively  through  discussion  /  question and answer with monitoring during  the extension  / dissemination of the material presented during the process of  counseling /  socialization  takes place  between  the  participants in the material  renderer. Of implementation, it can be  produced  the conclusion that  the management  had understood the concept of village institutions and policies outline the rules governing the content of  the GOI, has understood mechanisms and normative regulations  in the management of  village institutions  and  have  understood  the position of  rural community participation  in management activities of institutional by members of the village by village in the district secretaries  forum Jatiagung South Lampung regency. Keywords: Aparateur Capacity, Villages Institution